The conciliation movement in the Cape Colony during the Anglo-Boer War, 1899-1902 - Botma, Trudé (Department of Historical Studies, 2016)
The conciliation movement at the Cape was largely the offshoot of a parent body in England. This factor tempts the researcher to compare the one with the other, a practice which produces the most frustrating results. Unlike their English counterparts, the conciliators at the Cape did not form a clearly defined, centrally directed, organisation. They were, on the contrary, members of a loosely knit alliance of like-minded persons. Although the movement resulted from the stimulus of a number of leading figures, it had a large and varied supporting cast and there were even individuals who were not formally associated with it who played a leading role in its activities. The term conciliation movement therefore covers a very wide range and there is a voluminous amount of material available in connection with it. There are, however, also the most tantalising lacunae in the available information. In dealing with the conciliation movement I have attempted to concentrate on the activities of its English-speaking associates, as it was they who gave it its essence, but as it drew the bulk of its support from the Dutch section of the colonists their activities cannot be ignored.